Financial Stress-Test of the Palm Oil Industry: Bankruptcy Prediction Using the Modified Altman Z-Score During the Downturn Phase - Harke Revo Leonard Polii; Sandra J.R. Kainde; Rifal Richard Pangemanan (STIE Amkop Makassar, 2026)
This study aims to predict the bankruptcy potential of Plantation Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) during the critical downturn cycle of 2017-2019. This period serves as a stress-test window following the commodity boom. Employing a descriptive quantitative approach, the research analyzes secondary data from 10 companies selected through purposive sampling. The primary analytical tool is the Modified Altman Z-Score model. The results indicate severe financial distress within the sector due to price volatility and aggressive downstreaming policies. Specifically, out of the 10 sampled companies, only 1 company was classified as